Systematic Review: Effectiveness of Probiotic Giving as Additional Therapy in Atopic Dermatitis Patient - Pangkahila, Evangelista Maria; Dewi, Made Yudha Asrithari; Harimawan, Agustinus I Wayan (PT BMW Journal Sejahtera, 2024)
Background: Atopic dermatitis (AD), also known as eczema, is a chronic inflammatory skin condition affecting the epidermis and dermis. It is triggered by a combination of environmental and genetic factors, leading to symptoms such as polymorphic rashes and intense itching. Objective: This systematic review aims to evaluate the effectiveness of oral probiotic supplementation as an adjunct therapy for individuals with atopic dermatitis. Methods: The literature was reviewed by searching two electronic databases, Google Scholar and PubMed, resulting in the inclusion of eight studies that collectively involved 347 AD patients. Results: The findings indicate that probiotic supplementation can significantly reduce the severity and incidence of atopic dermatitis. This effect is attributed to the inhibition of Th2 cell activity and a reduction in pro-inflammatory cytokines, including TNF-α and IgE, which are known contributors to the pathophysiology of AD. Conclusion: Probiotics present a promising alternative for the prevention and management of atopic dermatitis, potentially enhancing patient outcomes.